Percepção de vaidade e beleza em adultos, idosos e longevos - Duarte, Carlos Eduardo de Oliveira (2020)
Aging is the result of the natural course of time that leads to physiological, mental and social changes, as everyone will experience it gradually. Understanding the centrality of beauty and positive vanity is an important aspect of adaptive processes in all stages of life, but especially in older adults, being linked to the quality of adaptation, well-being, satisfaction with life and health. Positive vanity is not related to chronological age, but to the quality of social integration and the adaptive capacity of people to deal with life events, including the changes involved in the aging process. The present study aimed to identify the perceptions about vanity and beauty of groups of people of different ages. The methodology adopted a qualitative, quantitative, descriptive, exploratory approach, through a questionnaire and interviews applied to 16 adults, 14 elderly and 10 long-lived, in the city of Passo Fundo (RS). Three scientific productions resulted from the study. The first aimed to identify the perception of vanity and beauty of men and women from 40 to 79 years old. The second sought to describe the perception of vanity and beauty for long-lived elderly. The information obtained was synthesized by Bardin's content analysis. The productions show that, although at different ages, beauty and vanity refers to maintaining a positive attitude, valuing achievements, living new experiences, in a healthy and productive way, in which instigated new lifestyles, spaces and social roles. Vanity in aging can significantly increase the maintenance of self-care and self-esteem, developing and diversifying relationships, self-love and well-being, which are explored with greater vigor in knowledge, communication and social integration. It is the awareness of a subjective feeling, which reflects the inner beauty, externalized ability to live a healthy, active and productive life. It can be applied to more than physical beauty, on any aspect concerning opportunities, values and a differentiated understanding of the experiences, complexity and differential patterns of the aging process.